2016
DOI: 10.1016/j.bbr.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in attenuation of nicotine reinstatement after individual and combined treatments of progesterone and varenicline

Abstract: Tobacco use is the largest cause of preventable mortality in the western world. Even after treatment, relapse rates for tobacco are high, and more effective pharmacological treatments are needed. Progesterone (PRO), a female hormone used in contraceptives, reduces stimulant use but its effects on tobacco addiction are unknown. Varenicline (VAR) is a commonly used medication that reduces tobacco use. The present study examined sex differences in the individual vs. combined effects of PRO and VAR on reinstatemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 72 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…Sex differences are observed during all stages of nicotine addiction, from initiation to dependence, withdrawal, and relapse. The current Review evaluates sex differences observed in nicotine preference during exposure to nicotine, notwithstanding the fact that important sex differences have been reported during extinction or reinstatement of nicotine‐seeking (Feltenstein et al, ; Swalve et al, ). In laboratory animals, the methods used for evaluating individual differences in nicotine preference involve “asking” male and female animals if they like nicotine or not.…”
Section: Comparison Of the Three Animal Models Used To Study Nicotinementioning
confidence: 99%
“…Sex differences are observed during all stages of nicotine addiction, from initiation to dependence, withdrawal, and relapse. The current Review evaluates sex differences observed in nicotine preference during exposure to nicotine, notwithstanding the fact that important sex differences have been reported during extinction or reinstatement of nicotine‐seeking (Feltenstein et al, ; Swalve et al, ). In laboratory animals, the methods used for evaluating individual differences in nicotine preference involve “asking” male and female animals if they like nicotine or not.…”
Section: Comparison Of the Three Animal Models Used To Study Nicotinementioning
confidence: 99%
“…This suggests that relatively low doses of nAChR antagonists could be used to diminish cue-induced craving and prevent relapse in smokers. The smoking cessation drug varenicline inhibits reinstatement of operant responding induced by nicotine-prime and a combination of nicotine-prime and cues (O’Connor et al 2010; Swalve et al 2016). In contrast, bupropion potentiates cue-induced reinstatement of nicotine seeking (Liu et al 2008).…”
Section: Reinstatement Of Nicotine Seekingmentioning
confidence: 99%
“…Progesterone (PRO; Sigma Aldrich, St. Louis, MO) was dissolved in peanut oil (VEH; Sigma Aldrich) to a final dose of 0.5 mg/kg administered subcutaneously 30 minutes prior to experimental sessions. This dose has produced endogenously relevant levels of PRO (Jackson et al 2006), and it decreased cocaine-seeking and impulsivity for food and cocaine in our previous studies (see Anker et al 2011 for a review; Smethells et al 2016; Swalve et al 2016a, b, d; Zlebnik et al 2014). …”
Section: Methodsmentioning
confidence: 86%
“…In most animal studies, females exceed males on acquisition (Lynch and Carroll 1999; Jackson et al 2006; Lynch 2009; but see Caine et al 2004; Swalve et al 2016b; for review see Anker and Carroll 2011) and maintenance of cocaine self-administration (Lynch and Carroll 1999; Anker et al 2011; Cummings et al 2011; Peterson et al 2014; Swalve et al 2016c; but see Roberts et al 1989; Cosgrove et al 2002; Jackson et al 2006; Kosten and Zhang 2008; Perry et al 2013). Animal studies also indicate that females have a better response to PRO treatment for cocaine self-administration than males (Carroll and Lynch 2016; Carroll and Smethells 2016).…”
Section: Introductionmentioning
confidence: 99%